Dasar dan Implikasi Putusan Mahkamah Konstitusi Nomor 83/PUU-XXII/2024 terkait Pembatalan Perjanjian Asuransi secara Sepihak oleh Perusahaan Asuransi - Aan Prayoga; Rizky Utama; Mohamad Ashiddiqi; Reagen Awaloei (Jurnal Hukum Lex Generalis, 2025)
The Constitutional Court Decision No. 83/PUU-XXII/2024 declares Article 251 of the Indonesian Commercial Code conditionally unconstitutional. Consequently, annulment of contracts, particularly insurance agreements, is unconstitutional unless based on mutual consent between the insurer and the insured, or by court ruling. The Court emphasized that Article 251 contradicts principles of justice, legal certainty, and consumer protection guaranteed by the 1945 Constitution. This decision reinforces that annulment of insurance contracts cannot be imposed unilaterally but must reflect a fair balance of rights, thus strengthening constitutional protection for consumers in contractual relations.